TASHKENT STATE UNIVERSITY OF LAW EXPANDS INTERNATIONAL COLLABORATIONS WITH KEY PARTNERS - Doniyor Abduazizov; Ismigul Kubaeva (European Science Publishing, 2025)
Tashkent State University of Law (TSUL) continues to strengthen its global presence by forging new academic partnerships with leading institutions in Japan and South Korea. These collaborations, marked by agreements with Yokohama National University and the establishment of the Korea Law and Research Center, aim to enhance academic mobility, foster international research, and provide students and faculty with broader educational and professional opportunities. This article highlights TSUL’s latest initiatives in advancing legal education on an international scale.